Nitrate is safe to feed ad libitum in molasses roller drums as a source of non-protein nitrogen - Goopy, John P.; Hegarty, Roger S. (Commonwealth Scientific and Industrial Research Organisation, 2019)
We investigated voluntary intake, growth and safety of cattle offered low-quality forage diets plus isonitrogenous molasses-based liquid supplements containing either urea (U) or a calcium nitrate-containing compound (NO3). We hypothesised that changing the nitrogen source from U to calcium nitrate would not jeopardise animal health or affect intake. Angus cattle (n = 24) were allocated to six pens, with three pens each receiving a molasses supplement containing U or a molasses supplement containing NO3 for 31 days. There was a trend (P = 0.06) for the NO3 treatment group to consume more of the (oaten chaff) basal diet than the U treatment group. The U group consumed more supplement than did the NO3 group (1.31 vs 0.40 kg DM/head.day s.e.m. = 0.094, P < 0.0001), but total DM intake was not different (6.45 vs 6.10 kg/head.day, P = 0.15). Mean final animal liveweight was not different between treatments. Methaemoglobin levels were higher in the NO3 group (2.1 vs 1.3%, P < 0.001). Low consumption of nitrate was also reflected in there being no effect of nitrate on the methane production rate when assessed in open-circuit calorimetry chambers (7.1 vs 7.0 g/head.2 h, P = 0.898). It is confirmed that nitrate may be safely provided to cattle when dissolved at 154 g/kg in a molasses-based liquid supplement available ad libitum, but may not be an effective methane mitigant due to low NO3 intake. It is speculated that nitrate may be a useful tool to limit voluntary intake of non-protein nitrogen supplements.